The Effect of Tempe Dietary Intake on Plasma Glucose Level in Elderly Patients with Type 2 Diabetes Mellitus - Puspasari, Grace; Dillon, Drupadi; Budiman, Budiman (Journal of Medicine and Health, 2017)
The aim of the study was to investigateÂ  the effect of daily intake of 100 grams tempe for four weeks on plasma glucose level in elderly patients with type 2 diabetes mellitus. This study was a parallel randomized clinical trial. Subjects were 30 diabetic elderly living in four nursing homes in Jakarta. In the study subjects were assigned to two groups using block randomization. All subjects had to take diabetic regiment with calorie and macronutrient following diabetic recommendation diet. The treatment group (n=16) received tempe, while control group (n=14) received legumes other than tempe. Fasting plasma glucose level (FPG) was assessed before and after intervention. Unpaired t test and Mann Whitney were used to analyzed data with the 5% significance level. There were 27 subjects completed the study: 15 of treatment group and 12 of control group. Both group were comparable in age, gender, BMI, calorie and macronutrient intake before treatment. Fat, fiber, and isoflavone intake were significantly higher in treatment group compare to control group. Decrease in FPG after intervention were observed but were statisticaly insignificant. In conclusion daily intake of 100 grams tempe for four weeks did not decrease FPG. Â Keywords: elderly, plasma glucose level, tempe, type 2 diabetes